Pemberdayaan Ekonomi Kreatif Masyarakat Desa melalui Workshop Produk Rumah Tangga Sabun Cuci Piring dalam Perspektif Ekonomi Islam - Novan Wicaksana; Nuni Asnita Barasa; Muhammad Wirayuda; Erwan Efendi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2026)
Household spending on hygiene products often places an economic burden on low-income rural communities. Workshops on making liquid dish soap are one form of creative economic empowerment that can reduce spending while opening up opportunities for home-based businesses. This community service activity was carried out in Nagori Bandar Manik Village through counseling and hands-on practice in making liquid soap using easily obtainable ingredients. The results of the activity showed an increase in the community’s knowledge and skills in independently producing dishwashing soap. In addition, an economic analysis of the business showed that the production cost was Rp1,660 per package with a potential profit of Rp2,340 per unit, making it feasible to develop as a micro business. From an Islamic economic perspective, this program reflects the values of maslahah and ta’awun because it is able to maintain the sustainability of household economies and strengthen community independence. Thus, this activity is effective in increasing expenditure efficiency while encouraging the growth of creative home-based businesses.